# Put in algebraic equation: The difference of 3 times a number y and 2 equals 19.  I can't figure this out to help my daughter. Thanks

Posted on

3y-2=19

3y-2+2=19+2

3y=21

3y/3=21/3

y=7

Posted on

The concept of three times a number y and two equals 19 is simply written as

3y+2 = 19

To find the solution to this equasion you simply subtract 2 from each side which leaves you with 3y=17 .  At this juncture you divide each side by 3 and that gives you Y=17/3

The soultion would be  Y= 5 2/3

Posted on

3y-19=2

It is worded a little strangely, but what they are saying is that 3 times the unknown number is 19 more than 2.

Add 19 to each side of the equation; you then have 3y=21.

Divide each side by 3, and y=7

You could also look at it as 3y-2=19; add 2 to each side, and once again you have 3y=21

Posted on

The difference of 3 times a number y and 2 equals 19.

difference=subtract

times=multiply

y=?

i.e,

3y-2=19

3y=19+2

3y=21

y=21/3

Posted on

The difference of 3 times a number y and 2 equals 19 .

So first by reading this problem , we can tell that 2 and " y "  are multiplied . Later on we can tell that we want to find the difference of 3 times y and 2 . By doing that it would look like

3y - 2 We also know that we want the equation to equal to 19 , so it would look like

3y - 2 = 19 now we can solve this equation , first add 2 on both sides

By adding 2 on both sides , you should get

3y = 21 now we can divide both sides by 3 ,

by dividing both sides by 3 , you should get

Posted on

The difference of 3 times a number y and 2 equals 19

3y - 2 = 19

move like terms to the same side

3y = 19 + 2

3y = 21

divide by 3

y = 7

Posted on

The difference of 3 times a number y and 2 equals 19.

Difference = subtraction

times = multiplication

3 times a number y = 3y

Difference of 3 times a number y and 2 = 3y - 2

This equal 19 so

3y - 2 = 19

To solve:

3y = 19 + 2 = 21

y = 21/3 = 7

Posted on

The equation would be 3y+2=19

If you want to know the solution of the alegbraic equation, here it is:

3y+2=19

3y+2-2=19-2 (-2)

3y=17

3y/3=17/3 (divide 3)

y= 5 2/3 //